The Compatibility of the Theory of Gradational Unity and the Individual Unity of Existence - Morteza Hoseinzadeh; Tahereh Kamalizadeh (حکمت صدرایی, 2018)
Gradation of being is one of the important principles of transcendent philosophy. In this philosophy, compatibility and incompatibility between the individual unity of being and the gradation of being is one of the conflicts between commentators. According to gradation of being, gradation is in levels of being, and due to the individual unity of being; there is no gradation in levels. Since the real being is not more than one being and other things are its manifestations and aspects. Hence apparently there is an incompatibility between these two principles and it is not possible to accept both of them. Sadra, by accepting gradation of being, proves the individual unity of being. This paper poses two meaning for the unity of being by showing two types of gradation presented by Sadra. It is possible to prove typical unity according to particular gradation and the individual unity of being is resulted from special particular gradation (tashkik khasi). To fix this incompatibility, we can say that according to two gradation, Sadra believes on two kinds of unity that the individual unity of being cannot summed up with particular gradation, but special particular gradation(tashkik khasolـkhasi) is compatible with the individual unity of being.